Effects of various LED light colours on yield and physical characteristics of white oyster mushrooms / Siti Nur Fathiha Abdullah ... [et al.] - Abdullah, Siti Nur Fathiha; Yusoff, Hamid; Koay, Mei Hyie; Budin, Salina; Sh Abdul Nasir, Sh Mohd Firdaus (Universiti Teknologi MARA Cawangan Pulau Pinang, 2023)
Commercial mushroom farming in Malaysia predominantly focuses on grey oyster mushrooms, while white oyster mushrooms are comparatively less popular due to their slower growth rate. Previous studies have explored the effects of natural light on mushroom growth, but there is limited research on the use of artificial light in mushroom production. Therefore, this study investigated the influence of different LED light colours on the growth performance, yield and physical properties of white oyster mushrooms in a controlled mushroom chamber. The objective was to identify the optimum LED light colour to enhance yield and physical characteristics. In the experiment, mushroom blocks were exposed to various LED light colours, including white, warm white, blue, red, and green. The results indicated that exposure to blue light significantly increased both the yield and physical quality of white oyster mushrooms. In conclusion, blue LED light proved to be the most effective treatment for promoting the development of white oyster mushrooms.